Pelatihan Usaha Cuci Motor Plus Detailing Kendaraan untuk Peningkatan Keterampilan Warga Desa Roworejo - Dwi Jatmoko; Aci Primartadi; Arif Susanto; Bintang Fatia Wibowo; Mukhammad Abdul Wakhid; Purnawan Purnawan (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The purpose of this community service program is to improve the technical skills of residents of Roworejo Village, Grabag, Purworejo, in the field of motorbike washing and car detailing. Improving technical skills to wash motorbikes and detail vehicles according to professional standards and the application of technology that supports business sustainability through a water recycling system is the main focus of the activity. This activity is carried out by providing theoretical training on basic vehicle detailing techniques, as well as direct practice such as washing, body care, polishing, and the use of detailing tools. Participants are also educated on how to use and maintain a water recycling system when running a business. The results of the activity showed that 78% of participants succeeded in applying the principles of environmentally friendly technology in business practices. In addition, 85% of participants were able to master the basic techniques of washing motorbikes and detailing vehicles according to training standards. It is hoped that this activity will help sustainable village economic development and open up new skills-based business opportunities.